N-Heterocyclic carbenes as π*-acceptors in luminescent Re(I) triscarbonyl complexes - Casson, L.; Muzzioli, S.; Raiteri, Paolo; Skelton, B.; Stagni, S.; Massi, Massimiliano; Brown, David (The Royal Society of Chemistry, 2011)
Two rhenium(I) carbonyl complexes of the type fac-[Re(CO)3(N^C)X] where N^C is an N-heterocyclic carbene [3-butyl-1-(2’-pyridyl)benzimidazolin-2-ylidene] and X is either Cl or Br have been synthesised via an in situ method from [Re(CO)5X] and a respective benzimidazolium salt. The complexes have been characterised by 1H and 13C NMR, infra-red spectroscopy and in the case of the bromo-complex by a single-crystal X-ray diffraction study. The photophysical properties of the complexes have been investigated, revealing similar phosphorescent emission which was attributed to radiative decay from a 3MLCT state partially mixed with a 3LLCT state. However, the analysis of excited state lifetime and quantum yield values revealed distinct photophysical behaviour for the two complexes, which was attributed to the more labile nature of the bromo ligand with respect to the chloro one. The explanation was supported by the time-dependent emission profile change in diluted acetonitrile solutions.